MODERN PEDAGOGICAL TECHNOLOGIES AND ITS NEED IN LANGUAGE TEACHING (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
In the course of this research, the stages of organizing the educational process using innovative technologies of teaching in modern society were analyzed. Nowadays, the interest and attention to the use of interactive methods, innovative technologies, modern pedagogical and information technologies in the educational process is increasing year by year. Therefore, we will discuss this issue in the following article.